Comparison of Strain-Specific Antibody Responses During Primary and Secondary Infections With Respiratory Syncytial Virus - Scott, Paul D. (J Med Virol, 2007)
Respiratory syncytial virus (RSV) is a major cause of lower respiratory tract infection in infants. RSV repeatedly reinfects individuals: this may be due in part to the variability of the attachment (G) glycoprotein and changes in this protein have been shown to be under positive selection. Infants experiencing their primary infection show a genotype-specific antibody response with respect to the variable regions of the G protein. A prospective study of RSV infections in a birth cohort in rural Kenya identified infants experiencing repeat infections with RSV. The serum antibody responses of these infants were investigated with respect to their anti-RSV reactions in an enzyme-linked immunosorbent assay (ELISA) and the specificity of the response to a variable region of the G protein by ELISA and immuno-blotting using bacterially expressed polypeptides representative of the currently circulating strains of RSV. The results presented here confirm that the primary antibody response to the variable regions of the G protein is generally genotype-specific, but show that the response may become cross-reactive (at least within group A viruses) during secondary infections even where the secondary infection is of the same genotype as the initial infection. Also, some infants who did not mount a detectable antibody response to whole RSV antigens during their primary infection nevertheless showed genotype-specific responses to the G protein. In conclusion, the strain-specific nature of the serum antibody response to the variable regions of the G protein of RSV observed in primary infections can become cross-reactive in subsequent reinfections.